Type III secretion system confers enhanced virulence in clinical non-O1/non-O139 Vibrio cholerae. (October 2019) - Zeb, Samia; Shah, Muhammad Ali; Yasir, Muhammad; Awan, Hassaan Mehboob; Prommeenate, Peerada; Klanchui, Amornpan; Wren, Brendan W.; Thomson, Nicholas; Bokhari, Habib
Abstract: Vibrio cholerae O1 infections mainly are responsible for significant mortality and morbidity amongst children, however, non-O1/non-O139 V. cholerae have also been reported to cause mild to severe infections because of their virulence potential. The pathogenic mechanisms of non-O1, non-O139 isolates are not as clearly understood as for that of O1 and O139 isolates. Type three secretion system (TTSS) is also considered one of the important virulent factors and during the current study, we investigated the role of TTSS in association with non-O1/non-O139 clinical isolates. We report that the presence of TTSS in non-O1/non-O139 V. cholerae clinical isolate (D13) from a child confers more virulence compared to the one lacking it (D15) in another clinical case during the small cholera epidemic. Moreover, the antibiotic susceptibility profiles of D13 and D15 indicate that they are multiple drug resistance (MDR) isolates. The sequence analysis for TTSS cluster was carried out for D13 and compared with the TTSS positive reference Vibrio parahaemolyticus RIMD2210633 and V. cholerae AM19226 non-O1/non-O139. Furthermore, the pathogenic potential of D13 & D15 was also explored in simple and economical invertebrate host model, Galleria mellonella and the results revealed that TTSS +ve isolate (D13) was more virulent compared to TTSS -ve isolate (D15). We suggest that this distinct genetic difference, seen in natural variants D13 and D15, is also reflected by the clinical picture of the former in contributing towards the severity of disease symptoms and this finding was further validated by assessing virulence potential of both isolates using inexpensive G. mellonella infection model. Highlights: TTSS is considered an important virulent factor and here we investigated the role of TTSS in association with non-O1/non-O139 clinical isolates. This article report that the presence of TTSS in non-O1/non-O139 V. cholerae clinical isolate (D13) from a child confers more virulence. The antibiotic susceptibility profiles of D13 and D15 indicate that they are multiple drug resistance (MDR) isolates. The results revealed that TTSS+ve isolate (D13) was more virulent compared to TTSS-ve isolate (D15). These finding was further validated by assessing virulence potential of both isolates using inexpensive G. mellonella infection model.